Community Capacity Building in Organic Waste Management through The Takakura Method - Muhamad Kaka Milano; Alda Febriyanti; Muhammad Gelar Gumelar; Chika Amaria; Hazmi Hazmi; Adisty Maharani; Arya Ahmudika; Muhamad Vito Nur Zaki; Fatra Syahlan; Rema Mulyani (Siber Nusantara of Community Service Review, 2026)
The problem of household organic waste is still a major challenge in environmental management in urban areas, including in Jayaraksa Village, Sukabumi City. The low level of knowledge and skills of the community in managing waste has led to an increase in the volume of waste disposed of in temporary shelters. This Community Service Activity (PKM) aims to increase community capacity in organic waste management through the application of the Takakura method. The method used is Participatory Action Research (PAR) with the stages of problem identification, planning, implementation, and monitoring and evaluation involving active community participation. The results of the activity show an increase in community knowledge and skills in managing organic waste, as well as changes in behavior in sorting and processing waste at the household level. The implementation of the Takakura method has proven to be effective in reducing the volume of organic waste and producing compost that can be used as organic fertilizer. In addition to having a positive impact on the environment, this program also has the potential to support a community-based circular economy.